Cancer Care During COVID-19 Era: The Quality of Life of Patients With Thyroid Malignancies - Falcone, Rosa; Grani, Giorgio; Ramundo, Valeria; Melcarne, Rossella; Giacomelli, Laura; Filetti, Sebastiano; Durante, Cosimo (Frontiers in Oncology, 2020)
Background: The Covid-19 pandemic's potential psychological impact has been widely discussed on the basis of expert opinion and previous experience with emergencies of this type. We conducted a survey of cancer patients to explore more objectively the outbreak's impact on their emotional well-being and quality of life. Methods: Between March 18 and April 4, 2020, at an endocrine cancer center in Rome, Italy, 137 patients were asked to complete an online 6-item questionnaire developed by our staff to explore the emotional effects of the Covid-19 outbreak in Italy (Covid-19 Emotional Impact Survey, C-19EIS). For validation purposes, we also asked participants to complete an online version of the validated Italian translation of the EORTC QLQ-C30 questionnaire. Responses were analyzed in relation to responders' age, sex, and clinical status (advanced/metastatic disease undergoing systemic treatment vs. stable metastatic thyroid cancer in active surveillance vs. low-risk thyroid cancers with no evidence of structural disease during standard follow-up). Results: Response rates were high (51% for the C-19EIS, 44.5% for the EORTC QLQ-C30). Overall C-19EIS scores indicated high concern over the outbreak (median 8/12). Scores were higher in women (8 [IQR 5–9] vs. 6 [IQR 5–8] in men; p = 0.048) and in patients <65 years (8 [IQR 5–9] vs. 6 [IQR 4–8] in older patients; p = 0.013). No differences emerged across clinical status groups. C-19EIS scores were inversely correlated with the EORTC QLQ-C30 Emotional function subscale (rho −0.69; p < 0.001). Conclusions: There is objective evidence that the Covid-19 outbreak is causing substantial emotional distress among cancer patients, regardless of their disease severity or current health-care needs.